Job design research and theory: Past, present and future - Oldham, Greg R.; Fried, Yitzhak (Organizational behavior and human decision processes, 2016)
•We review early work in the area of job design.•We analyze contemporary research that has expanded our knowledge of job design.•We discuss several directions for future research in the area of job design. This article reviews the research and theory that have focused on the design of jobs in organizations. We begin by summarizing some of the earliest work on this topic and then move to a discussion of several approaches to job design that attempted to address the shortcomings of this work. Next, we discuss several streams of contemporary research that have expanded the scope or deepened our understanding of job design. We conclude with a discussion of some future directions for research with an emphasis on job crafting, the effects of new work arrangements on the design of jobs, generational differences and reactions to job design, cultural differences and job design, and the impact of job design on organizational structures and employees’ personal characteristics.